2004
DOI: 10.1136/adc.2003.031104
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of alcohol hand rub and gloves reduces the incidence of late onset infection in very low birthweight infants

Abstract: Objective: To assess the incidence of late onset (. 72 hours) infection and necrotising enterocolitis (NEC) in very low birthweight (VLBW) infants in two 36 month periods using two hand hygiene protocols: conventional handwashing (HW; first 36 month period); an alcohol hand rub and gloves technique (HR; second 36 month period). Method: VLBW infants admitted to the neonatal intensive care unit during the period December 1993-November 1999 were eligible. A new hand hygiene protocol using alcohol handrub and glov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 30 publications
1
42
0
1
Order By: Relevance
“…Preterm infants who developed NEC had threefold increased risk of mortality (4). As the immunologic defense of preterm infants is considered to be immature and/or deficient (5), this category of patients is particularly vulnerable to developing severe and opportunistic infections in the immediate postnatal period (1,3,4). However, early warning signs and symptoms of systemic infection and NEC are often nonspecific and inconspicuous and can easily be confused with noninfective causes such as apnea of prematurity, gastrointestinal dysmotility, and acute exacerbation of bronchopulmonary dysplasia (6 -8).…”
Section: Ate-onset (ͼ72 H Of Life or Nosocomial) Bacterial Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preterm infants who developed NEC had threefold increased risk of mortality (4). As the immunologic defense of preterm infants is considered to be immature and/or deficient (5), this category of patients is particularly vulnerable to developing severe and opportunistic infections in the immediate postnatal period (1,3,4). However, early warning signs and symptoms of systemic infection and NEC are often nonspecific and inconspicuous and can easily be confused with noninfective causes such as apnea of prematurity, gastrointestinal dysmotility, and acute exacerbation of bronchopulmonary dysplasia (6 -8).…”
Section: Ate-onset (ͼ72 H Of Life or Nosocomial) Bacterial Infectionmentioning
confidence: 99%
“…and NEC are important risk factors that predispose to increased morbidity and mortality in preterm VLBW infants (1)(2)(3)(4). A recent multicenter survey suggested that 21% of VLBW infants who survived Ͼ72 h of age had at least one episode of septicemia (1).…”
Section: Ate-onset (ͼ72 H Of Life or Nosocomial) Bacterial Infectionmentioning
confidence: 99%
“…890 In several other studies in which hand hygiene compliance was not monitored, multidisciplinary programmes that involved the introduction of an alcohol-based handrub were associated with a decrease in HCAI and cross-transmission rates. 429,489,645,735 The beneficial effects of hand hygiene promotion on the risk of cross-transmission have also been reported in surveys conducted in schools or day-care centres, 454,[891][892][893][894][895][896] as well as in community settings. 248,249,449,754,815,830,[897][898][899][900] While none of the studies conducted in the health-care setting represented randomized controlled trials, they provide substantial evidence that increased hand hygiene compliance is associated with reduced HCAI rates.…”
Section: Impact Of Improved Hand Hygienementioning
confidence: 99%
“…Three studies demonstrated a decrease in infection rates with the hand sanitizer. 21,24,25 Two other studies 22,23 reported no significant differences in HCAI rates between handwashing and the introduction of a hand sanitizer. Another study 26 reported a decrease in MRSA rates postintervention.…”
Section: Category 2 Hand Hygiene Productsmentioning
confidence: 99%
“…In 5 of these studies, one before and after design with no control group 21 and 4 cohort studies with control groups [22][23][24][25] compared handwashing with the introduction of an alcohol hand sanitizer. Another before and after study with control group 26 compared the 4% antiseptic solution with the introduction of a 1% antiseptic solution.…”
Section: Category 2 Hand Hygiene Productsmentioning
confidence: 99%